The impact of ABO blood type on the prevalence of portal vein thrombosis in patients with advanced chronic liver disease. (4th March 2020) - Scheiner, Bernhard; Northup, Patrick G.; Gruber, Anselm B.; Semmler, Georg; Leitner, Gerda; Quehenberger, Peter; Thaler, Johannes; Ay, Cihan; Trauner, Michael; Reiberger, Thomas; Lisman, Ton; Mandorfer, Mattias
Abstract: Background and aims: Non‐O blood type (BT) is a risk factor for thromboses, which has been attributed to its effects on von Willebrand factor (VWF)/factor VIII (FVIII) levels. Although high VWF/FVIII may be risk factors for portal vein thrombosis (PVT) in patients with advanced chronic liver disease (ACLD), the impact of BT on PVT is unknown. We aimed to assess (I) whether non‐O‐BT is a risk factor for PVT and (II) whether non‐O‐BT impacts VWF/factor VIII in patients with ACLD. Methods: Retrospective analysis comprising two cohorts: (I) " US " including all adult liver transplantations in the US in the MELD era and (II) " Vienna " comprising patients with a hepatic venous pressure gradient (HVPG) ≥6 mmHg. Results: (I) The " US cohort " included 84 947 patients (non‐O: 55.43%). The prevalence of PVT at the time of listing (4.37% vs 4.56%; P = .1762) and at liver transplantation (9.56% vs 9.33%; P = .2546) was similar in patients with O‐ and non‐O‐BT. (II) 411 patients were included in the "Vienna cohort" (non‐O: 64%). Mean HVPG was 18(9) mmHg and 90% had an HVPG ≥10 mmHg. Patients with non‐O‐BT had slightly increased VWF levels (318(164)% vs 309(176)%; P = .048; increase of 23.8%‐23.9% in adjusted analyses), but this difference was driven by patients with less advanced disease. However, non‐O‐BT explained only 1% of the variation in VWF and had no effect on FVIII. Conclusions: Although non‐O‐BT impacts VWF in patients with early stage ACLD, its contribution to VWF variation is considerably smaller than in the general population. Moreover, non‐O‐BT had no impact on FVIII. These findings may explain the absence of an association between non‐O‐BT and PVT in patients with advanced cirrhosis.